Strategy of of economic efficiency enhancement for land use of aviation transport - Novakovska, I.; Skrypnyk, L. (Land Management, Cadastre and Land Monitoring, 2019)
The issue of forming an effective land use system for aviation transport, which aims at obtaining a certain volume of material goods with minimum capital and energy costs, as well as achieving maximum productivity of natural resources use and environmental protection of the natural environment, was considered.Operation of the aviation industry is an extraordinary economic contribution to the level of productivity of other industries, which is a powerful fixative for their growth. Such influence, in turn, contributes to the increase of the productivity level of the world economy.It was substantiated that the economic evaluation of efficiency is a very important concept, which aims to determine the most optimal for the airline labor costs and capital, profit, compensation, use of labor, material and, above all, land resources as an indisputable territorial basis. One of the first issues that reveals the level of economic efficiency of land use of aviation is revenue (profit) as a result.The main economic indicators of the efficiency of land use of aviation transport port, calculated with the obligatory consideration of the area of the land plot and the specific period of time during which the given land was exploited: the potential of land use; land use intensity, land use efficiency and insurance risk assessment.The main ways to increase the level of economic performance of land use of aviation transport are to improve the structure of investments and the planning of infrastructure development in areas where the expansion of industrial and commercial facilities is possible. This investment strategy also aims to reduce the amount of residential development in areas near airports, as these objects are incompatible with each other.Keywords: aviation transport land use, economic efficiency indicator, improvement and development strategy.